PENGARUH PELATIHAN TERHADAP KEBERHASILAN PROGRAM SUSTAINABLE LIVELIHOOD: PERAN MEDIASI KESIAPAN BERUBAH SERTA MODERASI KARAKTER INDIVIDU DAN DUKUNGAN PEMERINTAH - Ranti Rurina; Ahmad Shalahuddin; Rizky Fauzan (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the influence of training on the success of the Sustainable Livelihood program through the role of mediation of readiness to change as well as the moderation of individual character and government support in assisted communities around Gunung Palung National Park, North Kayong Regency. Methods: The study used a quantitative approach with an explanatory design. Data was collected through a questionnaire to 62 respondents of community members assisted by the Sustainable Livelihood program and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the help of SmartPLS 4.0. Results: The results showed that training had a positive and significant effect on readiness to change, and readiness to change had a positive and significant effect on the success of the Sustainable Livelihood program. Individual character was also shown to positively moderate the relationship between readiness to change and program success, whereas government support did not show a significant moderation effect. These findings contribute to the development of conservation-based community empowerment literature by showing that the success of Sustainable Livelihood programs is not only determined by training, but also by the readiness of individuals to adopt change.